5x-6-2x=4x+8

Simple and best practice solution for 5x-6-2x=4x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-6-2x=4x+8 equation:


Simplifying
5x + -6 + -2x = 4x + 8

Reorder the terms:
-6 + 5x + -2x = 4x + 8

Combine like terms: 5x + -2x = 3x
-6 + 3x = 4x + 8

Reorder the terms:
-6 + 3x = 8 + 4x

Solving
-6 + 3x = 8 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-6 + 3x + -4x = 8 + 4x + -4x

Combine like terms: 3x + -4x = -1x
-6 + -1x = 8 + 4x + -4x

Combine like terms: 4x + -4x = 0
-6 + -1x = 8 + 0
-6 + -1x = 8

Add '6' to each side of the equation.
-6 + 6 + -1x = 8 + 6

Combine like terms: -6 + 6 = 0
0 + -1x = 8 + 6
-1x = 8 + 6

Combine like terms: 8 + 6 = 14
-1x = 14

Divide each side by '-1'.
x = -14

Simplifying
x = -14

See similar equations:

| 6x+6=6x-9 | | 2/3(6x+9)=18 | | -8v=-80 | | -2(-x-8)=2x+15 | | -3(x-5)+12x=9(x+2)+12 | | 60+15=4 | | d-16=-50 | | 2(6w+8)=2(4w+24) | | (3x+5)=2(x+7) | | -6(x-8)=48 | | n+t+g+h=106 | | 162=11x+19 | | 3(x+5)+4x=-(x-5) | | x-1=-4*1 | | 34+4k=102 | | 15=3xy-1 | | 0.75n-3=-9 | | 2/3+4=8 | | 64=4v | | M=1/k+n | | W=x-y/2 | | 3x-8x-4=8x | | j/6-9=5/9 | | x-27=43 | | (x-3/5)^2+y^2-9=0 | | 27.3m-45.1=-13.2+6.8 | | 4(y+2)=5(y-6) | | (x-3/5)2+y2-9 | | 4(11X+4)=44X-2 | | 7x-1=-36 | | 8x=-80 | | 4.1(4x-2.5)=-3.5 |

Equations solver categories